Using Turbo Basic - Mosher, Frederick E.; Schneider, David I. (California : Osborne McGraw-Hill, 1988)
This book serves a broad range of users. It will be particularly helpful for beginning and intermediate programmers, and those who have used other BASIC compilers or other programming languages, but are new to turbo basic.
1. Introduction to turbo basic -- 2. A first look at turbo basic -- 3. The turbo basic editor -- 4. Manipulating data -- 5. Decision and repetition -- 6. Functions and procedures -- 7. Data files -- 8. Graphics and sound -- 9. A closer look at the turbo environment -- 10. Compiler directives and system-level tools -- 11. Mathematics and scientific programming -- 12. Business programming.
Includes bibliographical references and index.
Keywords: COMPUTER LANGUAGES PROGRAMMING